Legislating the Female Body: Reproductive Technology and the Reconstructed Woman - Karpin, Isabel (Columbia Journal of Gender and Law, 1992)
Legal conceptions of the female body tend to assume a singular, uncontested, received idea of the “nature” of that body. I argue, on the contrary, that in the process of regulating the female body, the law legislates its shape, its lineaments, and its boundaries. However, law does not act alone to fix the shape of the female body. It collaborates with other defining discourses such as science and popular culture. The effect of this collaboration is to blur the lines of influence, enabling each discourse to refer to the other to substantiate its claim about the “nature” of the female body. This paper is concerned with the intersection between these discourses and with challenging those premises about women that arise as a result of this insistence by law and legal discourse on an omnipresent female body that “we”‘ all know, understand, and agree upon.